Response of MC3T3-E1cells on microroughen bioactive glass coated zirconia - Tuladhar, Sapna Laxmi; Parajuli, Umesh; Wang, Hang (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The objective of this study was to determine the cellular response of micro-roughened bioactive glass coated zirconia substrate (ZBR) and non roughen bioactive glass coated zirconia substrate (ZB), and compare them with uncoated zirconia substrate (Z). Materials & Methods: Surface micro-roughening was obtained using an Al2O3 sandblasting method. Abrasive blasting of zirconia coated bioactive glass produced an irregular finish with surface roughness average Ra 0.85 µm as determined by profilometer and scan electron microscope. Surface roughness of the samples in ascending order was ZBR>ZB>Z. Murine derived preosteoblast (MC3T3-E1) cells were seeded on the samples, and the cell morphology, growth, differentiation, were observed. Cell morphology was evaluated by means of scanning electron microscope (SEM), while cell proliferation and differentiation using MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) test and alkaline phosphates activity respectively. Results: The cell growth on all the samples continual increase with culturing up to 5days, showing good cell viability. However, there was no significant difference (p>0.05) with respect to the Z, ZB, and ZBR at day 5 at MTT assay. In particular, the alkaline phosphatase (ALP) activity of the cells was significantly higher on the ZB and ZBR than Z samples at both 7 and 14 days. Conclusion: Our ﬁndings demonstrate that bioactive glass coated surface was found to have better surface conditions to regulate bone cell differentiation